Recognition of Streptococcal Promoters by the Pneumococcal SigA Protein - Solano-Collado, Virtu; Ruiz-Cruz, Sofía; Lorenzo-Díaz, Fabián; Pluta, Radoslaw; Espinosa, Manuel; Bravo, Alicia (Frontiers in Molecular Biosciences, 2021)
Promoter recognition by RNA polymerase is a key step in the regulation of gene expression. The bacterial RNA polymerase core enzyme is a complex of five subunits that interacts transitory with one of a set of sigma factors forming the RNA polymerase holoenzyme. The sigma factor confers promoter specificity to the RNA polymerase. In the Gram-positive pathogenic bacterium Streptococcus pneumoniae, most promoters are likely recognized by SigA, a poorly studied housekeeping sigma factor. Here we present a sequence conservation analysis and show that SigA has similar protein architecture to Escherichia coli and Bacillus subtilis homologs, namely the poorly conserved N-terminal 100 residues and well-conserved rest of the protein (domains 2, 3, and 4). Further, we have purified the native (untagged) SigA protein encoded by the pneumococcal R6 strain and reconstituted an RNA polymerase holoenzyme composed of the E. coli core enzyme and the sigma factor SigA (RNAP-SigA). By in vitro transcription, we have found that RNAP-SigA was able to recognize particular promoters, not only from the pneumococcal chromosome but also from the S. agalactiae promiscuous antibiotic-resistance plasmid pMV158. Specifically, SigA was able to direct the RNA polymerase to transcribe genes involved in replication and conjugative mobilization of plasmid pMV158. Our results point to the versatility of SigA in promoter recognition and its contribution to the promiscuity of plasmid pMV158.